Community capacity and the reporting of extortion victimization - Dulin, Adam (International journal of comparative and applied criminal justice, 2025)
The present research examines the impact of actualised collective efficacy on the probability of reporting extortion victimisation in Mexico. The mechanisms that encourage crime reporting have been an important area of study for years, however the specific factors that increase the probability of reporting extortion have eluded examination. The analysis extends the concept of collective efficacy, adapting it to contexts where actual informal social control effects can be examined. Therefore, the present study moves beyond perceptions and measures knowledge of, and participation in, such neighbourhood activities. The statistical analysis of 3,453 cases of extortion revealed that both actualised collective efficacy and participation in informal social control were strong predictors of reporting extortion victimisation to authorities after controlling for 20 other potentially confounding variables.